ChemInform Abstract: KNa3Mn7(PO4)6: 2D Spin‐Frustrated Magnetic Material with a Diamond‐Like Chain Structure. Issue 40 (30th September 2014) - Guo, Wenbin; He, Zhangzhen; Zhang, Suyun; Yang, Ming; Tang, Yingying; Cheng, Wendan
Abstract Single crystals of the title compound are prepared by solid state reaction of Na2CO3, Mn(OAc)2, NH4H2PO4, and KF (alumina crucible, 1153 K, 40 h).